Considering Death Penalty for Corruptors in Law on Corruption Eradication from the Perspective of Maqāṣid al-Syarī‘ah - Asa’ari, Asa’ari; Ahmad, Jafar; Zufriani, Zufriani; Witro, Doli; Kustiawan, Muhamad Taufik (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2023)
The implementation of the death penalty for corruptors has never been decided by any judges throughout the history of law enforcement in Indonesia. However, Law No. 31 of 1999 jo Law No. 20 of 2001 on Corruption Eradication has established the criteria or conditions for a corruptor to be sentenced to death. This was an empirical legal study which was conducted by library research. This article examines judge decisions by a descriptive analysis. The theory used in this research was maqāṣid al-syarī‘ah. The paradigm was used to determine the dynamics of Islamic law in analysing the death penalty for corruptors. This study was based on the Social Assistance (Bansos) corruption committed by former Minister of Social Affairs, Julia Peter Batubara, during the Covid-19 pandemic. The corruption was committed by Julia Peter Batubara when there was an epidemics and national economic crisis. This study found that the death penalty for corruptors is affected by political power, allowing corrupt officials to escape the death penalty.